Science on Youtube: Successful Edutubers - Pattier, Daniel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
The growing use of video as an educational resource and of the YouTube platform in our society leads us to investigate the impact of educational YouTube Science channels and the success factors and variables used by edutubers in this area. Through the analysis of the 41 most successful educational channels of Sciences on YouTube Spain, we obtain results on different aspects of the process of creation and dissemination of audiovisual content. The conclusions indicate a high impact of the YouTube channels of Sciences and a positive trend, anticipating a great projection of edutubers and educational audiovisual content in this area of knowledge. In addition, the success factors and variables used by edutubers in their channels are pointed out. Our research provides insights for teacher training plans and YouTube educational content creators.